Návrh optimalizace daňové povinnosti fyzické osoby - podnikatele - Čoupek, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Tato bakalářská práce se zabývá návrhem optimalizace daňové povinnosti fyzické osoby - podnikatele. Zvolenou optimalizační metodou je koexistence živnostenského podnikání fyzické osoby a podnikání fyzické osoby jako jediného společníka společnosti s ručením omezeným. V návaznosti na teoretické poznatky je tato metoda aplikována na konkrétního poplatníka.

This bachelor’s thesis deals with the optimalization proposal regarding tax lability for a self-employed person. The chosen optimalization method is a coexistence of an individual proprieting and natural person’s entrepreneurship being the only companion in a Limited Liability Company. In keeping with the theoretical knowledge of this method, it is used in connection with a concrete taxpayer.
Optimalization Proposal Regarding Tax Lability for a Sefl-employed Person
Keywords: společnost s ručením omezeným; fyzická osoba - podnikatel; daň z příjmů; daňová optimalizace; Limited Liability Company; self-employed person; income tax; tax optimalization